The Effect of Using WhatsApp Groups on Elementary School Students Learning Motivation - Asri Ranreng; Muh. Yunus; Andi Annisa Sulolipu; Muqtakdir Nurfalaq Syarif (JURNAL PENDIDIKAN IPS, 2023)
ABSTRACT This study aimed to determine an overview of the use of the WhatsApp group at SDN 22 Soreang, Minasatene District, Pangkep Regency, and overview of the learning motivation of high grade students and the effect of using the whatsApp group on motivation study high class students at SDN 22 Soreang, Minasatene District, Pangkep Regency. This type of research is a quantitative descriptive research. The population in this study were all students, totaling 108 people. The sampling technique in this study was purposive sampling, so that the research sample was 56 people. The data collection technique used was the distribution of questionnaires and documentation techniques. The data analysis technique was carried out using descriptive analysis in the form of percentages and inferential analysis using analysis prerequisite tests and hypothesis testing (t-test). The results showed that the description of the use of the whatsApp group at SDN 22 Soreang, Minasatene District, Pangkep Regency tended to be in the fairly good category, where descriptively a percentage value was obtained of 41%, an overview of the learning motivation of high grade students at SDN 22 Soreang Minasatene Subdistrict, Pangkep Regency tends to be in the good category, where descriptively a percentage value of 32% was obtained and there was a significant effect of the use of the whatsApp group on the learning motivation of high class students at SDN 22 Soreang, Minasatene District, Pangkep Regency, where the probability value was smaller than the significant level (0.018 <0.05).